BOB CAT: a Large‐Scale Review and Delphi Consensus for Management of Barrett's Esophagus With No Dysplasia, Indefinite for, or Low‐Grade Dysplasia. (May 2015) - Bennett, Cathy; Moayyedi, Paul; Corley, Douglas A; DeCaestecker, John; Falck‐Ytter, Yngve; Falk, Gary; Vakil, Nimish; Sanders, Scott; Vieth, Michael; Inadomi, John; Aldulaimi, David; Ho, Khek‐Yu; et al.
Abstract : OBJECTIVES: Barrett's esophagus (BE) is a common premalignant lesion for which surveillance is recommended. This strategy is limited by considerable variations in clinical practice. We conducted an international, multidisciplinary, systematic search and evidence‐based review of BE and provided consensus recommendations for clinical use in patients with nondysplastic, indefinite, and low‐grade dysplasia (LGD). METHODS: We defined the scope, proposed statements, and searched electronic databases, yielding 20, 558 publications that were screened, selected online, and formed the evidence base. We used a Delphi consensus process, with an 80% agreement threshold, using GRADE (Grading of Recommendations Assessment, Development and Evaluation) to categorize the quality of evidence and strength of recommendations. RESULTS: In total, 80% of respondents agreed with 55 of 127 statements in the final voting rounds. Population endoscopic screening is not recommended and screening should target only very high‐risk cases of males aged over 60 years with chronic uncontrolled reflux. A new international definition of BE was agreed upon. For any degree of dysplasia, at least two specialist gastrointestinal (GI) pathologists are required. Risk factors for cancer include male gender, length of BE, and central obesity. Endoscopic resection should be used for visible, nodular areas. Surveillance is not recommended for <5 years of life expectancy. Management strategies for indefinite dysplasia (IND) and LGD were identified, including a de‐escalation strategy for lower‐risk patients and escalation to intervention with follow‐up for higher‐risk patients. CONCLUSIONS: In this uniquely large consensus process in gastroenterology, we made key clinical recommendations for the escalation/de‐escalation of BE in clinical practice. We made strong recommendations for the prioritization of future research.